Near-infrared quantum cutting luminescence in Pr3+/Yb3+ doped lead bismuth borate glass - Seshadri, Meruva; Santos, Ilza T. C.; Bell, Maria Jose V.; Lapointe, Jerome; Messaddeq, Younes [UNESP]; Anjos, Virgilio (Springer Nature, 2022)
In this paper, thermally stable lead-bismuth-borate glasses were doped with 0.5 mol% of Pr3+ ions at several concentration levels of Yb3+ ions. Structural characterizations were performed via Raman, differential scanning calorimetry, optical absorption and fluorescence spectra. The Judd–Ofelt intensity parameter, Ω 2, of Pr3+ doped glass was comparatively higher than those from reported ones, which reflects the increase of co-valency and asymmetry of chemical bonds in the local environment of Pr3+. Near-infrared emission in 900–2200 nm wavelength range was recorded through 443 nm blue laser pumping. Visible to near-IR quantum cutting and concentration quenching mechanisms were discussed to understand the luminescent behaviour. Intense IR emission (∼1.0μm) features generated by absorbing one visible photon leads to quantum efficiencies close to 128% in Pr3+/Yb3+ co-doped samples which may improve the solar spectrum absorption and accordingly, increase the efficiency of c-Si solar cells. Emission cross-section, lifetime, figure of merit and gain bandwidth corresponding to Pr3+: 3F2→ 3H4 (∼2.0μm) were comparatively reported suggesting that the glass with molar composition 0.5Pr3+/0.1Yb3+ might be a potential candidate for ∼2.0μm laser operation with low pump threshold.